Exploring the Associations Between Momentary Gambling Motives and Gambling Behavior: An Ecological Momentary Assessment Study - Hawker, Chloe; Dias, Stephanie; Merkouris, Stephanie; Rodda, Simone; Dowling, Nicki (American Psychological Association, 2025)
OBJECTIVE: Drawing on the dynamic model of relapse, this study examined real-time relationships between momentary gambling motives (enhancement, coping, social, financial) and gambling behavior (episodes, expenditure, duration), as well as the moderating role of stable (problem gambling severity, high-risk situations) and momentary (psychological distress, emotion dysregulation, distress intolerance, state impulsivity) vulnerability factors, and the concordance between stable (Gambling Motives Questionnaire-Financial) and momentary measures of gambling motives. METHOD: A convenience sample of 132 Australian adults who endorsed gambling in a typical month (Mage = 29.9 years; 58.3% male; 94.7% endorsed gambling problems) completed a 28-day ecological momentary assessment protocol, involving twice-daily smartphone assessments of momentary variables and gambling episodes, following a pre-ecological momentary assessment survey of stable variables. RESULTS: Mixed-effects ordinal logistic regression analyses revealed that momentary coping (OR = 2.03), enhancement (OR = 1.73), and social motives (OR = 1.57) predicted increased gambling expenditure. Mixed-effects binary logistic regression analyses revealed that longer gambling duration predicted increased momentary financial motives (OR = 3.31), though financial motives did not predict gambling behavior. Individuals with distress intolerance were more likely to report a subsequent gambling episode when coping or enhancement motives were endorsed. No other factors showed significant moderating effects. Stable and momentary motives were strongly correlated (rs = 0.71-0.89), supporting the validity of single-item ecological momentary assessment measures relative to both the corresponding Gambling Motives Questionnaire-Financial item and subscale. CONCLUSIONS: These findings underscore the importance of momentary motives, particularly coping and enhancement, and emotional vulnerability in understanding gambling behavior in real time. Interventions targeting these dynamic processes and integrating distress tolerance training may enhance harm reduction efforts. (PsycInfo Database Record (c) 2025 APA, all rights reserved).
Keywords: 52 Psychology; 5203 Clinical and Health Psychology; 5201 Applied and Developmental Psychology; Basic Behavioral and Social Science; Behavioral and Social Science; Mental Health; 3 Good Health and Well Being; 1701 Psychology; Substance Abuse; 5202 Biological psychology; gambling; motives; reasons; distress tolerance; ecological momentary assessment; Humans; Gambling; Male; Adult; Ecological Momentary Assessment; Female; Motivation; Adaptation, Psychological; Psychological Distress; Middle Aged; Australia; Young Adult; Emotional Regulation; Impulsive Behavior; Humans; Adaptation, Psychological; Impulsive Behavior; Gambling; Motivation; Adult; Middle Aged; Australia; Female; Male; Young Adult; Ecological Momentary Assessment; Psychological Distress; Emotional Regulation; Humans; Gambling; Male; Adult; Ecological Momentary Assessment; Female; Motivation; Adaptation, Psychological; Psychological Distress; Middle Aged; Australia; Young Adult; Emotional Regulation; Impulsive Behavior